Analisis Usability Pada Aplikasi Ayoowork Baliyoni Menggunakan Use Questionnaire - Wicaksana, Putu Aryasuta; Swamardika, Ida Bagus Alit; Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro, 2021)
Abstract — Basically, building a system is to meet the needs of its users, where the system must consider the ease, comfort, and satisfaction of using the information system. Several studies have shown that these aspects can be measured through usability analysis. This research was conducted to analyze the usability of a project management information system developed and used at PT. Baliyoni Saguna Group. The purpose of this study is to determine the level of usability of information systems or usability by measuring four aspects of usability, Measurements are made using the Use Questionnaire which is measured using a Linkert scale with a scale of 5. So it is hoped that this research in the future can be a reference for companies to continue to develop information systems to support business activities and increase company competitiveness. The results of the study indicate that the Ayoowork Baliyoni information system has a good usability level with a score interpretation value of 62.07%. The scores of each aspect measured are usefulness with a score of 593 or 62.94%, ease of use 61.39%, ease of learning 60.59%, and satisfaction with 63.03%.